Some Remarks on the KP System of the Camassa-Holm Hierarchy - Giovanni Ortenzi (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We study a Kadomtsev-Petviashvili system for the local Camassa-Holm hierarchy obtaining a candidate to the Baker-Akhiezer function for its first reduction generalizing the local Camassa-Holm. We focus our attention on the differences with the standard KdV-KP case.